Season of birth and atopic dermatitis in early infancy: results from the Japan Environment and Children's Study - Akiko Tsuchida; Toshiko Itazawa; Kenta Matsumura; Hiroshi Yokomichi; Zentaro Yamagata; Yuichi Adachi; Hidekuni Inadera; on behalf of the Japan Environment and Children's Study Group (BMC, 2023)
Abstract Background Atopic dermatitis (AD) is reported to be more prevalent in children who were born in autumn than in spring. Here, we investigated how early the association between season of birth and eczema or AD can be observed in the postnatal period. We also examined whether specific prevalence outcomes for infant eczema and AD differed according to sex and maternal history of allergic disease in a large Japanese cohort. Methods Using data of 81,615 infants from the Japan Environment and Children's Study, we examined the associations of birth month or season with four different outcomes-eczema at 1 month, 6 months, and 1 year of age and physician-diagnosed AD up to 1 year of age-using multiple logistic regression analysis. We also analyzed the effect of maternal history of allergic disease on these outcomes stratified by infant sex. Results The risk of eczema at 1 month was highest in infants born in July. In contrast, infants born in autumn had higher risks of eczema at 6 months (adjusted odds ratio [aOR], 2.19; 95% confidence interval [CI], 2.10-2.30) and at 1 year (aOR, 1.08; 95% CI, 1.02-1.14) and of physician-diagnosed AD up to 1 year of age (aOR, 1.33; 95% CI, 1.20-1.47) compared with infants born in spring. Eczema and AD were more prevalent in infants with a maternal history of allergic disease, particularly boys. Conclusions Our findings suggest that the prevalence of AD is associated with the season of observation. Eczema is prevalent in infants born in autumn, and this phenomenon was observed in infants as young as 6 months old. The risk associated with being born in autumn was particularly clear in boys with a maternal history of allergic disease. Trial registration UMIN000030786